The Influence of Latin and Greek Elements on the Development of IT Terminology in the Kazakh Language - Kenges, B.E. (Karagandy University of the name of academician E.A. Buketov, 2025)
The purpose of the article is to determine the influence of Latin and Greek on the Kazakh IT terminology. In accordance with the tasks of the article, a review of the theory of borrowed words was conducted, the Greco- Latin roots were identified, and the frequency of use in the dictionary was determined. The study examined the relationship of classical languages with others and their role in the formation of scientific language. The influence of Latin and Greek borrowed words on Kazakh and the ways of their penetration were considered. The dictionary “Informatics and Computing Technology” (2014), containing 10,060 terms, served as study material. The article used a comparative historical method to identify Greek and Latin roots and Microsoft Excel was used to determine the frequency of occurrence of the identified Greek and Latin roots in the dictionary. The study identified 352 Latin and 165 Greek roots. Analysis in Microsoft Excel revealed that Latin roots appear 3,909 times and Greek roots 2,501 times, making Latin roots 1.54 times more frequent. Greek roots, though less frequent overall, show higher productivity. Each Greek-rooted word appears 15.1 times on average, compared to 11.1 for Latin, making Greek roots 1.36 times more common per unit. Their higher frequency indicates widespread use in terminology. The study presents these findings in a diagram and discusses the phonological adaptation of Greek and Latin borrowings in Kazakh. In Kazakh IT terminology, Latin roots make up 17.6 % and Greek 11.2 %, with a combined share of 29 %. This reflects the international aspect of IT terms and highlights the need to advance Kazakh terminology development, proving language convergence under globalization. The formation of IT terminology in English contributes to the lexical convergence of the Kazakh with the Greco-Latin languages. Although Latin is regarded as a dead language, it still exerts influence on living languages.
Қазақ тіліндегі IT-терминологиясының дамуына латын және грек элементтерінің ықпалы
Влияние латинских и греческих элементов на развитие IT-терминологии в казахском языке
Keywords: IT terminology; Latin roots; Greek roots; borrowed words; absolute frequency